Prevalence and associations of an abnormal ankle-brachial index in systemic lupus erythematosus: a pilot study. Issue 12 (21st November 2003) - Theodoridou, A; Bento, L; D'Cruz, D P; Khamashta, M A; Hughes, G R V
Abstract : Background: Accelerated atheroma is a well recognised complication of systemic lupus erythematosus (SLE). Its aetiology is multifactorial and several methods may be used to detect early signs of atheroma. Methods: Patients aged ⩽55 years were screened using the ankle-brachial index (ABI). Ninety one patients aged ⩽55 years and fulfilling the revised American College of Rheumatology criteria for SLE were studied. The ABI was measured using a contour wrapped 12 cm cuff attached to a mercury sphygmomanometer and an 8 MHz Doppler probe in the arms and legs; a ratio of <1 was considered abnormal. Results: The mean (SD) age of the patients was 39.0 (9.2) years. Of the 91 patients studied, 34 (37%) had an abnormal ABI. Only one patient was mildly symptomatic. Abnormal ABI correlated with age but not with disease duration, cumulative steroid dosage, ECLAM score, or any other traditional risk factors for atherosclerosis. In comparison with population studies, the prevalence of an ABI<1 in the patients with SLE with a mean age of 39 years was similar to that in adults aged over 80. Conclusion: In this pilot study, patients with SLE with a mean age of 39 years had a high prevalence of an abnormal ABI. The ABI is a simple non-invasive tool for the early detection of accelerated atheroma in SLE.